Traumatic Brain Injury, Approach in the Emergency Service (Revista de Medicina Clinica, 2019)
Severe traumatic disease is a global pandemic and one of the main causes of death and disability, especially in the young and active population. Cranioencephalic traumatism (CET) represents a major health problem worldwide. Epidemiological reports show a high variability in their results, with a crude incidence rate ranging from 47.3 to 849 cases per 100,000 inhabitants / year for all ages and types of severity. The CDC estimates that approximately 2.5 million people suffer a traumatic brain injury each year in North America, of these individuals 283,000 are hospitalized and 52,000 die, which is related to one third of all deaths related to traumatic injuries. For this reason it is necessary to be clear about the knowledge about this pathology which triggers great consequences to our patients, impacting their personal, family, work and health development. In this work the subject is addressed to a timely attention based on therapeutic goals to be considered in the emergency area.
Keywords: Traumatic brain injury; Emergency services; Initial care